Assessing the availability of the teratogenic drug isotretinoin outside the pregnancy prevention programme: a survey of e‐pharmacies1. (3rd February 2014) - Lagan, Briege M.; Dolk, Helen; White, Bronagh; Uges, Donald R. A.; Sinclair, M.
ABSTRACT Purpose The increase in online purchasing of medications raises safety concerns regarding teratogenic drugs. The use of the teratogenic drug 'isotretinoin' for women of childbearing age requires strict adherence to the Pregnancy Prevention Programme (PPP), a risk minimisation measure imposed on prescribers and users. We sought to determine how readily consumers can purchase isotretinoin online and the associated safety procedures and information. Methods A descriptive cross‐sectional survey was conducted of 50 e‐pharmacies identified from commonly used search engines. E‐pharmacy characteristics and isotretinoin PPP specific criteria were evaluated. Purchases of isotretinoin from seven e‐pharmacies not bearing authentication logos and not requiring a prescription were assessed for PPP policy adherence, purchasing procedures and compound quality. Results Forty‐three (86%) of the e‐pharmacies did not have an authentication seal/logo. Isotretinoin could be purchased from 42 sites without a valid prescription. Information on isotretinoin causing birth defects was lacking in 25 of the 50 sites, on not taking isotretinoin in pregnancy in 24 sites and not taking isotretinoin if planning or at risk of a pregnancy in 33 sites. Of the eight attempted purchases, seven arrived, all without any patient information leaflet. All were verified as isotretinoin. Conclusion The Internet provides a loophole for purchasing of medications known to cause congenital abnormalities, which needs to be addressed by medicines regulatory agencies worldwide. The current PPP for isotretinoin may be failing to protect mothers and babies from preventable harm—clinicians need to be aware of this, and the public needs to be educated about the potential risks. © 2014 The Authors. Pharmacoepidemiology and Drug Safety published by John Wiley & Sons, Ltd.